Structural, electronic, topological and vibrational properties of a series of N-benzylamides derived from Maca (Lepidium meyenii) combining spectroscopic studies with ONION calculations - Chain, Fernando Ezequiel (2016)
In the present work, the structural, topological and vibrational properties of four members of the N-benzylamides series derived from Maca (Lepidium meyenii) whose names are, N-benzylpentadecanamide, N-benzylhexadecanamide, N-benzylheptadecanamide and N-benzyloctadecanamide, were studied combining the FTIR, FT-Raman and 1H and 13C-NMR spectroscopies with density functional theory (DFT) and ONION calculations. Furthermore, the N-benzylacetamide, N-benzylpropilamide and N-benzyl hexanamide derivatives were also studied in order to compare their properties with those computed for the four macamides. These seven N-benzylamides series have a common structure, C8H8NO-R, being R the side chain [-(CH2)n-CH3] with a variable n number of CH2 groups. Here, the atomic charges, molecular electrostatic potentials, stabilization energies, topological properties of those macamides were analyzed as a function of the number of C atoms of the side chain while the frontier orbitals were used to compute the gap energies and some descriptors in order to predict their reactivities and behaviors in function of the longitude of the side chain. Here, the force fields, the complete vibrational assignments and the corresponding force constants were only reported for N-benzylacetamide, N-benzyl hexanamide and N-benzylpentadecanamide due to the high number of vibration normal modes that present the remains macamides.